Telaah Naratif Pentakostal tentang Karunia Nubuat dalam 1 Korintus 14 - Tambunan, Debora Tiurlan (P3M STT Kristus Alfa Omega, 2025)
The gifts of the Spirit are gifts given by the Holy Spirit to believers and one of the gifts of the Spirit written in 1 Corinthians is the gift of prophecy. However, this gift is often misunderstood in its application or ignored so that it is not empowered optimally in the congregation, especially in the Pentecostal community. This study aims to find out what the true meaning of the gift of prophecy is and what aspects of the gift of prophecy are in the ministry of the Corinthian church through qualitative biblical methodology. There are two distinct benefits derived from the gift of prophecy for the church as the body of Christ, namely, to build up (concerning faith), to admonish (concerning love), and to console (concerning hope). This study concludes that the gift of prophecy has important benefits for both believers and unbelievers, but its practical aspects need to be considered, especially in its use in the Pentecostal community.